Karakteristik dan Kadar Kolesterol Masyarakat di Padukuhan Tegalsari, Pakembinagun, Yogyakarta: Demographic Characteristics and Cholesterol Levels in the Community of Padukuhan Tegalsari, Pakembinagun, Yogyakarta - Fransisca Anjar Rina Setyani; Chatarina Setya Widyastuti; Hiasinta Anastasia Purnawijayanti (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Developments in food technology and community income have had an impact on people's eating habits. People prefer fast food, which is often high in calories and fat but low in fiber, leading to high blood cholesterol levels. High blood cholesterol levels cause blood vessels to harden and narrow, leading to atherosclerosis and increasing the risk of coronary heart disease. Other complications that can occur due to high blood cholesterol levels include stroke and peripheral artery disease. Objective: The purpose of this article is to provide an overview of the cholesterol levels of adults in Padukuhan Tegalsari, Pakembinagun, Yogyakarta. Methods: The research design used was descriptive. The population in this study was all members of the Gahtra Health Center, Tegalsari Village, Pakembinangun, Yogyakarta. The sampling technique used was accidental sampling. The number of samples in this study was 89 respondents. Result: The results showed that most respondents (52.8%) had very high cholesterol levels (> 200 mg/dL), 28.1% had high cholesterol levels (180-200 mg/dL), and only a small portion (19.7%) had normal cholesterol levels. Conclusion: Factors that may be associated with high blood cholesterol levels include age, gender, dietary patterns, and physical activity. Health workers should educate the public about factors that can be controlled to manage blood cholesterol levels. Education can be provided using engaging media to make it easier for the public to accept the information provided by health workers.